REASSESSMENT OF THE AGE OF BASEMENT IN THE VAVILOV BASIN DRILLED AT ODP SITE 651 (TYRRHENIAN SEA, MEDITERRANEAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
We carried out a biostratigraphic study based on calcareous nannofossils in sediments from Ocean Drilling Program (ODP) Site 651, drilled in the basalt-floored Vavilov sub-basin of the Tyrrhenian Sea (western Mediterranean) during Leg 107. The expedition achieved its primary objective to collect basement samples to date the ocean crust and obtain new data for reconstructing the geological evolution of the area. Studies on the ODP Site 651 succession determined the nature of the basement and provided time constraints for tectonic and magmatic processes in the basin, but contradictory lines of evidence emerged for the age of the basalts based on radiometric ages, paleomagnetic signature and planktonic foraminifera data. In an attempt to clarify the basement age, we performed detailed sampling for calcareous nannofossil analysis to update the biostratigraphy and chronology of the sediments overlying the basement. We determined the sediment accumulation rate using reliable nannofossil biohorizons that have a robust chronology, which increases up-section from ~ 2 cm/kyr to 3.4 cm /kyr. The age of the basalt/sediment contact was obtained through extrapolation of the sedimentation rate from the deepest datable portion of the sediments down to the top of basement. The inferred age for the top of the basalt is at least 4.1-4.2 Ma and differs from previous evaluations. This age for the basalt in the Vavilov Basin basement is consistent to a reversed interval C2Ar within the Gilbert magnetochron, supporting one of the chronologies previously proposed.
Keywords: Calcareous nannofossils; biochronology; ODP Site 651; Tyrrhenian Sea; basement age.